139P Multiplex IHC panel development for adenosine pathway markers and TIL in human cancer specimens. (15th December 2019) - Pabois, A; Bodo, V; Boisson, A; Crosignani, S; De Henau, O; Detheux, M; Garaud, S; Lager, J; Martinoli, C; Mercier, M; Naveaux, C; Thomas, N; et al.
Abstract: Background: Extracellular adenosine (Ado) is an immunosuppressive metabolite generated by the sequential activities of CD39 and CD73. High Ado, predominantly signaling through the A2A R, dampens immune responses and suppresses antitumor immunity. iTeos Therapeutics developed an A2A R antagonist, EOS100850, specifically designed to be a potent, highly selective and non-brain penetrant agent for treating a wide range of cancers. Methods: The development of mIHC is a high-powered practical approach for phenotyping and correlating cellular interactions in the tumor microenvironment, which can also be used to monitor the response to treatment. We have optimized a 6-color mIHC panel for A2A R, CD39, CD73, TNAP, Cytokeratin and DAPI using tonsillar and breast cancer (BC) specimens using detection reagents. We also used an immune mIHC panel (CD4, CD8, CD20, CD68, FoxP3, Cytokeratin). Serial sections of tonsillar and BC tissues were stained and imaged at 20X on the Vectra Polaris (Akoya) platform and analyzed with InForm. Results: Optimal dilutions for each antibody were first determined. A2A R staining was detected on immune cell subpopulations. CD39, CD73 and TNAP were expressed on immune cells and endothelial cells (EC). CD73 expression was elevated in Tertiary Lymphoid Structures. Then the order and pairing with an optimal fluorophore was examined. The relative positivity for the Ado pathway markers was accomplished first by full mIHC staining on tonsil tissues and subsequent validation on BC specimens. In BC tissues, A2A R, CD39 and TNAP expression was detected on various immune cell populations and EC. CD73 was additionally expressed by tumor cells. We also detected immune cells on BC tissue sections to characterize the cellular expression of Ado pathway markers, and to allow making correlations between expression of the Ado pathway markers and TIL infiltrate. Conclusion: We have established a specific mIHC protocol to identify the Ado pathway in cancer specimens. Characterization of Ado pathway markers in conjunction with infiltrating immune subpopulations in matched pre- and post-therapy patient specimens will now be investigated to identify specific tumors and treatments that will most likely benefit from combination therapy with EOS100850. Legal entity responsible for the study: iTeos Therapeutics. Funding: iTeos Therapeutics. Disclosure: A. Pabois: Full / Part-time employment: iTeos Therapeutics. V. Bodo: Shareholder / Stockholder / Stock options, Full / Part-time employment: iTeos Therapeutics. A. Boisson: Advisory / Consultancy: iTeos Therapeutics. S. Crosignani: Shareholder / Stockholder / Stock options, Full / Part-time employment: iTeos Therapeutics. O. De Henau: Full / Part-time employment: iTeos Therapeutics. M. Detheux: Shareholder / Stockholder / Stock options, Full / Part-time employment: iTeos Therapeutics. S. Garaud: Advisory / Consultancy: iTeos Therapeutics. J. Lager: Full / Part-time employment: iTeos Therapeutics. C. Martinoli: Full / Part-time employment: iTeos Therapeutics. M. Mercier: Full / Part-time employment: iTeos Therapeutics. C. Naveaux: Advisory / Consultancy: iTeos Therapeutics. N. Thomas: Advisory / Consultancy: iTeos Therapeutics. N. Wald: Full / Part-time employment: iTeos Therapeutics. A. Vezzu: Full / Part-time employment: iTeos Therapeutics. K. Willard-Gallo: Advisory / Consultancy: iTeos Therapeutics. E. Houthuys: Shareholder / Stockholder / Stock options, Full / Part-time employment: iTeos Therapeutics.